2006
DOI: 10.1044/1092-4388(2006/085)
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Phonotactic Probability and Neighborhood Density in Adult Word Learning

Abstract: Purpose The purpose of this study was to differentiate effects of phonotactic probability, the likelihood of occurrence of a sound sequence, and neighborhood density, the number of words that sound similar to a given word, on adult word learning. A second purpose was to determine what aspect of word learning (viz., triggering learning, formation of an initial representation, or integration with existing representations) was influenced by each variable. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
383
13
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(432 citation statements)
references
References 46 publications
33
383
13
3
Order By: Relevance
“…As an extension to the results of Masoura and Gathercole, our data show that serial order STM capacity remains an important predictor of foreign new word learning capacity, in addition to the influence of phonological knowledge for the given foreign language. These results also support the more general theoretical position offered by Metsala (1999) and Fowler (1990) (see also Storkel et al, 2006). This position considers that the increase of vocabulary knowledge in a given language favors segmentation and detailed representation of phonological knowledge, favoring in turn the acquisition of new phonological representations similar to that phonological knowledge.…”
Section: Phonological Knowledge and New Word Learningsupporting
confidence: 78%
See 2 more Smart Citations
“…As an extension to the results of Masoura and Gathercole, our data show that serial order STM capacity remains an important predictor of foreign new word learning capacity, in addition to the influence of phonological knowledge for the given foreign language. These results also support the more general theoretical position offered by Metsala (1999) and Fowler (1990) (see also Storkel et al, 2006). This position considers that the increase of vocabulary knowledge in a given language favors segmentation and detailed representation of phonological knowledge, favoring in turn the acquisition of new phonological representations similar to that phonological knowledge.…”
Section: Phonological Knowledge and New Word Learningsupporting
confidence: 78%
“…An effect of sublexical phonological knowledge on new word learning has also been shown in monolingual adults (Storkel, Armbruster, & Hogan, 2006). Similarly, new words having a large number of lexical phonological neighbours (familiar words that differ from the target word by a single phoneme addition, substitution or deletion) appear to be learned faster than new words with a low density lexical neighbourhood (Storkel et al, 2006).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, if the input does not have an exact match with existing lexical representations in long-term memory, the listener identifies the word as novel, initiating word learning. This process of initiating word learning is referred to as triggering (e.g., Storkel, Armbrüster, & Hogan, 2006). Note, it is assumed that the individual sounds and sound sequences in a novel word have a matching phonological representation, indicating that the sounds are known sounds rather than novel sounds such as in, for example, foreign language learning, where the listener may encounter novel sounds.…”
Section: Phonological and Lexical Representationsmentioning
confidence: 99%
“…Psycholinguistic experiments have shown that the network characteristic of degree influences in English the cognitive processes of word recognition [12], word production [20], and word learning [21]. (Note that in the psycholinguistic literature degree is referred to as neighborhood density.)…”
Section: Comparative Analysis Of English and Spanish Networkmentioning
confidence: 99%